Note—On Planning Freedom: Some Thoughts About the Ideas of Van Gigch - Nowakowska, Maria (Management Science, 1979)
This Note is an attempt at showing how the problem of planning for freedom discussed in (Eilon, S. 1976. Planning and freedom. Editorial. OMEGA, Internal. J. Management Sci. 4 (5) 501–505; Singhal, K., V. Vyasulu. 1978. More on planning for freedom. Management Sci. 24 (5) 581–584; van Gigch, J. P. 1976. Planning for freedom. Management Sci. 22 949–961; van Gigch, J. P. 1977. A management science approach to planning freedom—A Rejoinder. OMEGA, Internal. J. Management Sci. 5 (1)) can be formalized in terms of so-called “freedom functions” which express the distribution of rights in a society. It is argued that the approach analogous to that used in Arrow's Impossibility Theorem for social welfare functions would require determining first the class of all feasible freedom functions.